2008
DOI: 10.1111/j.1556-4029.2008.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Validation of a Cannabis sativa STR Multiplex System for Forensic Analysis

Abstract: A developmental validation study based on recommendations of the Scientific Working Group on DNA Analysis Methods (SWG-DAM) was conducted on a multiplex system of 10 Cannabis sativa short tandem repeat loci. Amplification of the loci in four multiplex reactions was tested across DNA from dried root, stem, and leaf sources, and DNA from fresh, frozen, and dried leaf tissue with a template DNA range of 10.0-0.01 ng. The loci were amplified and scored consistently for all DNA sources when DNA template was in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…All cases are originating from a period of 3 months in which they were brought to the analysing laboratory for THC concentration measurements. According to the number of alleles, the overall distribution is an interesting aspect because another Cannabis STR study found the lowest number of alleles for Cannabis STR systems ANUCS501 and B02 [6]. Mendoza et al [7] state that it was not possible to relate 98 Cannabis samples from 33 US states to each other.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All cases are originating from a period of 3 months in which they were brought to the analysing laboratory for THC concentration measurements. According to the number of alleles, the overall distribution is an interesting aspect because another Cannabis STR study found the lowest number of alleles for Cannabis STR systems ANUCS501 and B02 [6]. Mendoza et al [7] state that it was not possible to relate 98 Cannabis samples from 33 US states to each other.…”
Section: Discussionmentioning
confidence: 98%
“…The PCR reaction mix was run with 50 ng DNA, if not stated differently, in a total volume of 14.0 μl. The reaction mix contained 1.50 μl of MgCl 2 (50 mM), 0.2 μl of bovine serum albumin, 1.25 μl of AmpliTaq Gold buffer (10×), 0.15 μl AmpliTaq Gold, 1.25 μl of 10 mM dNTPs and each forward and reverse primer (changed according to [3,[5][6][7]) in a final concentration according to Table 1. The thermocycling started with 10 min at 95°C for the activation of the AmpliTaq Gold polymerase, followed by 25 cycles of (a) 95°C for 30 s, (b) 60°C for 30 s and (c) 72°C for 45 s. A final extension was held at 72°C for 30 min.…”
Section: Pcr Primers and Multiplex Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, este perfil químico não permite vincular produtores, a partir das características intrínsecas da planta 19 .…”
Section: Apesar De Encontrado Ao Redor Do Mundo Estudos Indicam Que unclassified
“…A great number of authors reported reliable methods for identification of cannabis samples, with possible application in retrieving information about the site of origin (Baker 1980;Crosby et al 1986;Brower 1994;Jagadish et al 1996;Linacre & Thorpe 1998;Datwyler & Weiblen 2006;Howard et al 2008Howard et al , 2009). Efforts to identify shipments of C. sativa through molecular profiles (Castro 2006;Mehmedic et al 2010), as well as through isotropic ratios (Shibuya et al 2006), have been conducted in Brazil; however, judiciary police agencies still do not have a standard operating procedure for this purpose.…”
mentioning
confidence: 99%